Arts in health: considering language from an educational perspective in the United States. Issue 2 (4th May 2018) - Sonke, Jill; B. Lee, Jenny; Helgemo, Max; Rollins, Judy; Carytsas, Ferol; Imus, Susan; Lambert, Patricia Dewey; Mullen, Tina; Pabst, Margery; Rosal, Marcia; Spooner, Heather; Walsh, Ian
Abstract: Background: There has been tremendous progress linking the arts to health over the past five decades in the United States. An academic discipline has been clearly established through the development of programs at accredited universities, a growing body of research and dedicated field journals. However, significant inconsistencies in the use of language to reference the discipline pose challenges for practitioners, educators, policy-makers, service users and the public, and may impede progress. Methods: This descriptive study investigated the language used to reference the discipline informed by literature review, technical examination of language, a field survey and round-table dialog among educators. Results: The literature review revealed "arts and health" as the most common term used, which also was the preferred term for the greatest number of survey respondents (26%), followed by "arts, health and well-being" (22%) and "arts in health" (21%), confirming a general lack of consensus. Technical examination of language identified certain terms or phases as problematic. Dialog among round-table participants yielded the recommendation for "arts in health" as the term that, for educational purposes, may best describe the overarching discipline and be inclusive of both health care and community-based practices. Conclusions: A recommendation is made for use of the term "arts in health" to reference the discipline in educational programs in the U.S.